Livros didáticos digitais, o governo brasileiro e a mídia: uma análise discursiva - Vizibeli, Danilo (Universidade Federal de São Carlos, 2019)
The general aim of this research is to analyze what was stated in the media about the implementation of digital textbooks in Brazilian public schools in order to understand the discourses to which they belong to, what was said and the effects of meaning aimed or actually produced. The corpus is constituted by news published in the online media and readers' comments on the National Textbook Program (PNLD), launched in 2013 and the Guide to the Didactic Book that, for the first time, concerned parameters of orientation, promotion and government acquisition of Digital Textbooks (LDd). The theoretical framework is the French Discourse Analysis in a Pêcheutian perspective, so that we can analyze what was actually stated about this event of the inclusion of digital textbooks in this notice and guide, as well as the way in which what was said was formulated and circulated, aiming or having produced certain effects of sense. For this, we analyze a set of statements in their relations of paraphrase or polysemy, depending on the discursive formation in which they are inscribed when they are enunciated. The analyzes allowed us to observe the strength of the paraphrase relations between statements coming from a technical-marketing discursive formation and those assumed by different subjects (journalists, teachers, students, etc.) who pronounced about this in the texts that constitute our corpus. The news published in the media divulges the event as a great advance in the Brazilian school scene, especially articulated to the reiteration of the discourse that proposes the deficiency of public education in Brazil. This alleged deficiency (and often real) acts as an argument to justify the importance of incorporating digital technologies, such as LDd supply, as well as to anticipate any difficulties in demonstrating their promised impact. Thus, public education agents are held accountable: given the difficult access to digital technologies by students and teachers from public school, they have, in particular, teachers with little training, habit and ability to work with this type of resource in the classroom. The speech is always ideological. From this, we can observe the words that circulated in recent years in the official media and in the media about textbooks in the digital version and the discursive relations that these sayings establish between themselves, (re) meaning educational practices. Thus, pedagogical discourses, advertising discourses pro-technological innovation, technical-economic discourses that populate the words of institutional origin (MEC), as well as the media texts that have repercussions on the event. In general, what is stated in this respect is marked by euphoric positions about the promotion of the production of the digital textbooks and its inclusion in the public school space. We support ourselves, especially in the following bibliographic reference: Michel Pêcheux (1997; 2002; 2009; 2011; 2015) and Eni Orlandi (2009; 2012) for the studies in Discourse Analysis; Roger Chartier (1991, 1998, 2002), Manguel (1997) and Robert Darnton (1992) on reading practices and the history of the book; and on textbooks (printed or digital) Célia Cassiano (2013) and Ednei Procópio (2013).
Keywords: Discurso; Livro didático; Livro digital; Leitura; Discourse; Textbook; Digital book; Reading; LINGUISTICA, LETRAS E ARTES::LINGUISTICA